2016
DOI: 10.1186/s12875-016-0468-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between multimorbidity patterns and chronic pain in elderly primary care patients: a cross-sectional observational study

Abstract: BackgroundMultimorbidity is a highly prevalent health problem, which may reduce adherence, produce conflicts in treatment, and is not yet supported by evidence-based clinical recommendations. Many older people suffer from more than one chronic disease as well as from chronic pain. There is some evidence that disease management can become more complex if multimorbid patients suffer from chronic pain. In order to better consider the patients’ comorbidity spectrum in clinical pain treatment recommendations, evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
81
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 27 publications
7
81
1
9
Order By: Relevance
“…Musculoskeletal pain is not only a common chronic condition in elderly patients in primary care [54] but also an important coexisting condition in medical inpatients with multimorbidity, as shown by our study results. Overall, hypertension was the most common condition (57.7%).…”
Section: Discussionsupporting
confidence: 61%
“…Musculoskeletal pain is not only a common chronic condition in elderly patients in primary care [54] but also an important coexisting condition in medical inpatients with multimorbidity, as shown by our study results. Overall, hypertension was the most common condition (57.7%).…”
Section: Discussionsupporting
confidence: 61%
“…Despite the fact that chronic pain is frequently addressed as a condition in itself our data support that it is indeed a bigger concern in RMDs in comparison to other conditions [22], both in terms of the magnitude of association (adjPR 1.69) and with regard to the fraction of chronic pain in the population that might be attributed to RMDs (PAF 15.2%).…”
Section: Discussionmentioning
confidence: 46%
“…A cross-sectional analysis of the elderly MultiCare Cohort Study sample found that chronic pain, as measured by the Graded Chronic Pain Scale 45 was largely associated with chronic lower back problems. 17 In our study, we were not able to distinguish if participants who reported problems to pain/discomfort had chronic or acute pain, neither were we able to determine the cause(s) of the participants' pain/discomfort. One may suffer from pain caused by the side-effects of medications, or from the discomfort caused by the disease(s).…”
Section: Discussionmentioning
confidence: 77%